2008
DOI: 10.1007/s10620-008-0399-3
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Placement Method of the Bravo Wireless pH Monitoring Capsule for Measuring Intragastric pH

Abstract: Our novel clipping method of the Bravo pH capsule placement provided accurate monitoring of intragastric pH with merits of tolerability, acid stability, and fixing position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Registration time is reported to be increased by securing the capsule onto the gastric wall by placing an endoscopic hemoclip on top of a thread tied to the capsule [11, 13, 14]. In our case, registration time was anyhow limited to 24 h, by allowing all data from the two parallel BRAVO™-capsules to be recorded on one receiver.…”
Section: Discussionmentioning
confidence: 99%
“…Registration time is reported to be increased by securing the capsule onto the gastric wall by placing an endoscopic hemoclip on top of a thread tied to the capsule [11, 13, 14]. In our case, registration time was anyhow limited to 24 h, by allowing all data from the two parallel BRAVO™-capsules to be recorded on one receiver.…”
Section: Discussionmentioning
confidence: 99%
“…44 In addition, catheter migration is an associated problem leading to inaccuracies. 45 To counteract this, the wireless capsule pH measurement system -BRAVO TM pH monitoring systemhas been utilised ( Figure 3). It can be inserted endoscopically, is better tolerated and can be used for a longer duration i.e.…”
Section: -38mentioning
confidence: 99%
“…A recent study that compares the BRAVO capsule system with the conventional catheter system found that the former enabled more stable and accurate pH monitoring (23). This study preferred the hemoclip technique as a method of BRAVO capsule attachment as it offers a low early drop rate (20%) (23). In our study, however, we directly attached the capsule to the gastric mucosa through a delivery unit, and 4 subjects (10.5%) had dropped in the early stage.…”
Section: Discussionmentioning
confidence: 73%
“…Compared with the conventional catheter method, it offers many benefits as it is more convenient for the patient, and stable pH measurement for 24 h or longer (up to 96 h) is available without any limitations to daily activities for the patient, such as in dining and exercise (21,22). A recent study that compares the BRAVO capsule system with the conventional catheter system found that the former enabled more stable and accurate pH monitoring (23). This study preferred the hemoclip technique as a method of BRAVO capsule attachment as it offers a low early drop rate (20%) (23).…”
Section: Discussionmentioning
confidence: 99%